The sphere of culture in the processes of nation-building and the consolidation of citizens: the experience of the cultural policy in France and Germany - I. I. Maslikova, (Ukrainian Cultural Studies, 2021)
The article examines the positive and negative experience of the consolidation of French and German citizens in process of nation-building by means of culture. The research deals with: practice of collecting masterpieces that influenced the development of public museums and the ability to defend national interests; the practice of consolidation of citizens around monuments of cultural figures; practices of confrontation between conservative intellectuals and modern artistic circles, which led to the fight against dissent, the destruction of books and the formation of the ideology of Nazism; practices of nazification of the education system, which revealed growing of the conflict between ideal virtues and the real behavior of participants in the educational process and politicians, and which subsequently legitimized absolute obedience to the leader; practices of collecting library collections, accompanied by theft of public libraries and private collections.The positive consequences of the consolidation citizens with the help of cultural institutions are indicated: the institutionally formed sphere of culture allows citizens to experience national pride, to be aware of themselves as a part of an original and rich national culture, to form their national identity. Cultural institutions create a space, which creativity is encouraged, opportunity for public discussions about culture and society are provided; educational and scientific activities are carried out.Recommendations on building a strategy for the cultural policy of Ukraine: the sphere of culture should be aimed at consolidating citizens; should expand the possibilities of various subjects of cultural activity and minimize the negative influences of the state; should expand access to quality education that fosters a culture of critical and creative thinking; should expand opportunities for international cooperation in educational and cultural projects based on the values of rights and freedom of individuals, mutual understanding and mutual respect of representatives of different cultures.
Keywords: the sphere of culture, cultural policy, the processes of nation-building, consolidation of citizens, cultural institutions